Fabrication and Characterization of a High-Gain Yb-Er Codoped Phosphate Glass Optical Amplifier - Gerardo Cristian Scarpignato; Daniel Milanese; Joris Lousteau; Nadia Giovanna Boetti; Emanuele Mura (Journal of Engineering)
We present the fabrication and characterization of a short core pumped fiber amplifier made of Yb3+-Er3+ codoped phosphate glasses. The 27 mm long amplifier provides a maximum internal gain of 10.7 dB for a signal of −30 dBm at 1535 nm with a 479 mW pump power operating at 975.6 nm. This leads to a gain of 4.0 dB/cm, which compares favorably to other recent works.